Manifestaciones de la hibridación en la forma y la representación dentro de los motion graphics como lenguaje audiovisual - Bohórquez Nates, Miguel (2018)
This thesis is the product of an investigation motivated by the need to develop a theoretical construction that would renew the conceptualization around the formal, representational, and stylistic manifestations of hybridization in motion graphics as a form of an audiovisual language. This work objective is to make a theoretical contribution to the study of motion graphics from a new perspective.\nTo this end, three main subjects are proposed in the definition of its internal functioning -specification of motion graphics as a form of language, demonstration of the specificity of hybridization in this form of language and the uses of this hybrid language-, which allows us to analyze the manifestations of hybridization as an essential aspect of their processes of production of meaning.